Genetic Control of Reproductive Traits in Tomatoes Under High Temperature - Gonzalo, Maria José; Li, Yi-Cheng; Chen, Kai-Yi; Gil, David; Montoro, Teresa; Nájera, Inmaculada; Baixauli, Carlos; Granell, Antonio; Monforte, Antonio José (Frontiers in Plant Science, 2020)
Global climate change is increasing the range of temperatures that crop plants must face during their life cycle, having negative effects on yield. In this changing scenario, understanding the genetic control of plant responses to a range of increasing temperature conditions is a prerequisite to develop cultivars with increased resilience. The current work reports the identification of Quantitative Trait Loci (QTL) involved in reproductive traits affected by temperature, such as the flower number (FLN) and fruit number (FRN) per truss and percentage of fruit set (FRS), stigma exsertion (SE), pollen viability (PV) and the incidence of the physiological disorder tipburn (TB) were investigated in 168 Recombinant Inbred Lines (RIL) and 52 Introgression Lines (IL) derived from the cross between Solanum lycopersicum var. “MoneyMaker” and S. pimpinellifolium accession TO-937. Mapping populations were cultivated under increased temperature regimen conditions: T1 (25ºC day/21ºC night), T2 (30ºC day/25ºC night) and T3 (35ºC day/30ºC night). The increase in temperature drastically affected several reproductive traits, for example, FRS in Moneymaker was reduced between 75 and 87% at T2 and T3 when compared to T1, while several RILs showed a reduction less than 50%. QTL analysis allowed the identification of genomic regions affecting these traits at different temperatures regimens. A total of 22 QTLs involved in reproductive traits at different temperatures were identified by multi-environmental QTL analysis and eight involved in pollen viability traits. Most QTLs were temperature specific, except QTLs on chromosomes 1, 2, 4, 6 and 12. Moreover, a QTL located in chromosome 7 was identified for low incidence of TP in the RIL population, which was confirmed in ILs with introgressions on chromosome 7. Furthermore, ILs with introgressions in chromosomes 1 and 12 had good FRN and FRS in T3 in replicated trials. These results represent a catalogue of QTLs and pre-breeding materials that could be used as the starting point for deciphering the genetic control of the genetic response of reproductive traits at different temperatures and paving the road for developing new cultivars adapted to climate change.